Aprendendo música com os Tupynambás: transmissão musical em uma Tribo Indígena Carnavalesca de Mandacaru, João Pessoa - Clemente, Marta Sanchis (2013)
Indian Carnival Tribe is the name of a cultural expression that traditionally participates into the city´s carnival of Joao Pessoa. Musical and danced staging of an Amerindian inspiriting ritual, represents a fight between Indians where the matança and the ressurreição are musically differentiated moments. This work studies, from an ethnomusicology perspective and so, focusing as much the artistic constitutive elements as the social, economic and politic context in which is inserted, the ways of its transmission. Thus, the main data collection tool is the participant observation achieved in the Mandacaru borough, where, currently, takes place the main group investigated, the Indian Carnival Tribe called Tupinambá. The present text is product of this ethnographic process as well as the result of a bibliographic research that follows two prevailing threads. One is the revision of the literature destined to Indian Carnival Tribes or Cabocolinhos,expression that shares characteristics and influences with the first one. The other is the looking for the concepts that provides the study theory basis brought, principally, from the area of ethnomusicology and music education. Providing a wider theoretical scheme for the analyses of music transmission in these contexts, Blacking, Nettl and Merriam supply the first theories. Some works of Brazilian researchers, as Margarete Arroyo and Luciana Prass, provided precious models of investigating in music transmission. The idea of participatory performance developed by Thomas Turino is the basis for the exam of how the elements that construct the artistic expression work as mechanisms of music transmission. The ideas of Shils and Hobsbawm about tradition and identity contribute to understand the signification that the play takes for their makers. Therefore, I aim to know how the very constitution of the activity, the participants way of life as well as the signification that this means to their makers, influence into the learning and the transmission processes of the same.